MAXIMIZING TEACHER DISCIPLINARY BEHAVIOR THROUGH RESPONSIBLE LEADERSHIP, A CORRELATIONAL STUDY - Ucok SAFARI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
This research is to study the correlation between responsible leadership of school principals and discipline of PKn (Civics) teachers at Al-Ashar Elementary School Pinang Sub-district, Tangerang City. Although there is a lot of study about the correlation between leadership and discipline, this study focuses on responsible leadership as opposed to “ordinary” leadership. The study used a correlation method where responsible leadership of school principals was used as an independent variable and discipline of PKn (Civics) teachers as the dependent variable. Thirty out of 35 teachers in the population were used as a random sample. Hypothesis testing was conducted using product moment. The study found that there is a positive correlation between the responsible leadership of school principal and Civics teachers at Al-Ashar Elementary School Pinang Sub-district, Tangerang City.